Open water scuba diving accidents at Leicester: five years' experience. Issue 3 (1st May 1999) - Hart, A J; White, S A; Conboy, P J; Bodiwala, G; Quinton, D
Abstract : OBJECTIVES: The aim of this study was to determine the incidence, type, outcome, and possible risk factors of diving accidents in each year of a five year period presenting from one dive centre to a large teaching hospital accident and emergency (A&E) department. METHODS: All patients included in this study presented to the A&E department at a local teaching hospital in close proximity to the largest inland diving centre in the UK. Our main outcome measures were: presenting symptoms, administration of recompression treatment, mortality, and postmortem examination report where applicable. RESULTS: Overall, 25 patients experienced a serious open water diving accident at the centre between 1992 and 1996 inclusive. The percentage of survivors (n = 18) with symptoms of decompression sickness receiving recompression treatment was 52%. All surviving patients received medical treatment for at least 24 hours before discharge. The median depth of diving accidents was 24 metres (m) (range 7-36 m). During the study period, 1992-96, the number of accidents increased from one to 10 and the incidence of diving accidents increased from four per 100, 000 to 15.4 per 100, 000. Over the same time period the number of deaths increased threefold. CONCLUSIONS: The aetiology of the increase in the incidence of accidents is multifactorial. Important risk factors were thought to be: rapid ascent (in 48% of patients), cold water, poor visibility, the number of dives per diver, and the experience of the diver. It is concluded that there needs to be an increased awareness of the management of diving injuries in an A&E department in close proximity to an inland diving centre.